2022
DOI: 10.3892/etm.2022.11640
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of HER2 status evaluation using immunohistochemistry in patients with urothelial carcinoma of the bladder: A retrospective single‑center experience

Abstract: In recent years, antibody-drug conjugate (ADC) therapy targeting human epidermal growth factor receptor 2 (HER2) has been proven to be beneficial in patients with advanced urothelial carcinoma of the bladder (UCB); however, the role of HER2 in UCB remains obscure. Thus, the present retrospective single-center study was performed to evaluate the expression of HER2 in UCB and its prognostic significance. The HER2 status of 108 patients with UCB who underwent radical cystectomy was assessed using immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A higher percentage of HER2+ expression is observed in high-grade UC. Bai et al (2022) conducted immunohistochemical staining to evaluate HER2 expression in 108 patients with bladder UC who underwent radical cystectomy. They discovered that 57.4% of patients exhibited HER2 overexpression, which was significantly correlated with elevated tumor grade ( p = 0.006) and staging ( p < 0.001) ( Bai et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher percentage of HER2+ expression is observed in high-grade UC. Bai et al (2022) conducted immunohistochemical staining to evaluate HER2 expression in 108 patients with bladder UC who underwent radical cystectomy. They discovered that 57.4% of patients exhibited HER2 overexpression, which was significantly correlated with elevated tumor grade ( p = 0.006) and staging ( p < 0.001) ( Bai et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“… Bai et al (2022) conducted immunohistochemical staining to evaluate HER2 expression in 108 patients with bladder UC who underwent radical cystectomy. They discovered that 57.4% of patients exhibited HER2 overexpression, which was significantly correlated with elevated tumor grade ( p = 0.006) and staging ( p < 0.001) ( Bai et al, 2022 ). A meta-analysis by Zhao et al (2015) also revealed a positive association between HER2 expression and high tumor grade.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators studied the HER2 positivity rate in UC and found that the rate varied, approximately ranging from 7% to 80%[ 17-26 ]. Studies examining the HER2 status and its prognostic value are summarized in Table 1 .…”
Section: Her2 Aberration In Ucmentioning
confidence: 99%
“…The HER2 status is significantly related to tumor stage and disease grade. In UC, HER2 expression is significantly increased in tumors of higher grades and stages[ 17 , 19 ]. A study discovered that tumors of a luminal molecular subtype had a significantly higher rate of HER2 alterations than those of a basal subtype, suggesting that HER2 activity is also associated with the subtype of tumors[ 18 ].…”
Section: Her2 Aberration In Ucmentioning
confidence: 99%